Improving the quality of midwife services with gentle birth - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2023)
Today, providing complementary care in health services for the community is increasingly mushrooming and is in great demand by all groups. The same is true for midwives. The midwife's duty as an extension of the government has resulted in the midwife having an obligation to take care of the condition of pregnant women until she gives birth, especially those related to maternal psychology. The gentle birth delivery method is one of the methods of delivery that supports government programs related to complementary and integrated health services. Through a gentle birth, the mother will feel valued, safe and comfortable, and the pain will be reduced. Evidence-based midwifery shows that if mothers are cared for and given support during labor, they will feel safe and comfortable so that the results will be better. Maternal love care is like allowing the mother to determine the desired position and movement during labor and birth. Midwives play a very important role. As advocates for mothers, midwives must ensure the needs of mothers, use adaptation skills, be flexible, and implement innovative practices to increase awareness of the services available to mothers.